2015
DOI: 10.1016/j.ijsu.2015.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing cold knife conization of the cervix with and without lateral hemostatic sutures

Abstract: Lateral hemostatic sutures do not affect the amount of intraoperative bleeding or the number of postoperative interventions. Their use is not necessary because they result in longer operative time, have a higher cost due to the use of suture material and pose the risk of ureter lesion in case the sutures are not placed at a lower position in the cervix. ClinicalTrials. gov identifier: NCT02184975.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Consistent with our results, another study by Letícia Rossi Bueno et al (22) investigated the cold-knife conization with and without sutures and found similar results. The authors found no difference in bleeding between the two groups of with and without sutures.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our results, another study by Letícia Rossi Bueno et al (22) investigated the cold-knife conization with and without sutures and found similar results. The authors found no difference in bleeding between the two groups of with and without sutures.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have explored different methods and techniques for reducing cold-knife conization complications. The reduction of operation duration for patients treated with non-suture techniques has also been reported in some studies (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…CKC requires general anesthesia, and bleeding is an important complication ( 20 ) . Despite many variations in the surgical technique ( 21 ) , we used the lateral hemostatic sutures at 3 and 9 o’clock positions, and the mentor described the proper borders with regard to the bladder and rectum to totally excise the dysplastic area.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical intraepithelial neoplasia (CIN) is a common precancerous lesion in women of reproductive age group worldwide [1]. Although no treatment is considered superior among the various excisional treatment modalities [1][2][3][4], the loop electrosurgical excision procedure (LEEP) has widely been preferred. This is because it can be performed under local anesthesia, it is easy to obtain specimens for pathological examination, and it has a high success rate with low major surgical morbidity rates [1,5].…”
Section: Introductionmentioning
confidence: 99%